On the relation between Pressure and Coupling Potential in Adaptive Resolution Simulations of Open Systems in contact with a Reservoir. Issue 1 (18th November 2021) - Gholami, Abbas; Klein, Rupert; Delle Site, Luigi
Abstract: In a previous paper, a precise relation between the chemical potential of a fully atomistic simulation and the simulation of an open system in the adaptive resolution method (AdResS) was identified. The starting point was the equivalence derived from the statistical partition functions between the grand potentials, Ω, of the open system and of the equivalent subregion in the fully atomistic simulation of reference. In this work, instead, the authors treat the identity for the grand potential based on the thermodynamic relation Ω = − p V $Ω =-pV$ and investigate the behavior of the pressure in the coupling region of the adaptive resolution method (AdResS). The authors confirm the physical consistency of the method for determining the chemical potential described by the previous work and strengthen it further by identifying a clear numerical relation between the potential that couples the open system to the reservoir on the one hand and the local pressure of the reference fully atomistic system on the other hand. Such a relation is of crucial importance in the perspective of coupling the AdResS method for open system to the continuum hydrodynamic regime. Abstract : The AdResS method was established by an earlier work as a computational framework to simulate open systems. In this paper, the authors successfully test a key feature of open systems that is the characterization of the grand potential through the equivalence of the system‐reservoir coupling potential and the balancing pressure at the interface.